Pengaruh Tangibility Asset, Size, dan Volatilitas Terhadap Financial Distress Pada Bumn di Bursa Efek Indonesia - Alvita, Devi; Kusumawardhani, Ratih; Sari, Pristin Prima (BRILIANT: Jurnal Riset dan Konseptual, 2024)
This research aims to determine the effect of asset tangibility, size and volatility on financial distress. In estimating financial distress in this research, the Altman Z-score model was used. With a sample size of 27 state-owned companies for 4 years or during COVID-19. The results of the analysis obtained are that the asset tangibility variable states that it has no effect on financial distress. Because, a high asset tangibility value will not necessarily prevent the company from financial distress. The size variable shows that it has no effect on financial distress. Companies that have a large number of assets will not necessarily avoid financial distress or financial difficulties. The volatility variable shows an influence on financial distress. Companies that have low volatility values ​​do not necessarily always experience financial distress or financial difficulties, and vice versa. This is because the volatility value will affect investors who will invest. This research concludes that state-owned companies listed on the Indonesia Stock Exchange for the 2019-2022 period or during the COVID-19 pandemic did not have a significant influence on financial distress. However, during COVID-19, banking and health companies made very rapid profits.